Role of clusters in exclusive breastfeeding practices in Tanzania: A secondary analysis study using demographic and health survey data (2015/2016) - Jahanpour, Ola Farid; Okango, Elphas Luchemo; Todd, Jim; Mwambi, Henry; Mahande, Michael Johnson (Frontiers in Pediatrics, 2022)
Background: While the benefits of exclusive breastfeeding are widely acknowledged, it continues to be a rare practice. Determinants for exclusive breastfeeding in Tanzania have been studied, however, the existence and contribution of regional variability to the practice have not been explored. Methods: Tanzania demographic and health survey data of 2015/2016 were used. Information on infants aged up to 6 months was abstracted. Exclusive breastfeeding was defined using a recall of feeding practices in the past 24 hours. Enumeration areas and regions were treated as random effects. Models without random effects were compared with those that incorporated random effects using an Akaike information criteria. The determinants of exclusive breastfeeding were estimated using a mixed model with enumeration areas nested within the region. Results: A mixed model with an enumeration area nested within a region performed better than other models. The intra-cluster variability at region and enumeration area levels was 3.7% and 24.5% respectively. The odds of practising exclusive breastfeeding were lower for older and male infants, for mothers younger than 18, among mothers residing in urban areas, among those who were employed by a family member or someone else, those not assisted by a nurse/midwife and not counselled on exclusive breastfeeding within 2 days post-delivery. There was no statistical evidence of an association between exclusive breastfeeding practices and frequency of listening to the radio and watching television. Conclusion: There is room to improve the proportion of those who practise exclusive breastfeeding in Tanzania. Beyond individual and setting factors, this analysis shows that a quarter of the variability in exclusive breastfeeding practices is at the community level. Further studies may explore what causes and how regional and enumeration area variabilities operate. Interventions to protect, promote and support exclusive breastfeeding in Tanzania may target the environment that shapes the attitude towards exclusive breastfeeding in smaller geographical areas.